Developmental language disorders: a longitudinal study of cognitive, social and psychiatric functioning - Clegg, Judy (2002)
A cohort of boys with developmental language disorders (DLD) have been followed up from childhood into adult life. At this most recent follow up, the DLD cohort was in their mid thirties (n = 17). The cohort was assessed on their cognitive, social and psychiatric functioning compared to their non language disordered siblings (n = 16), an intelligence quotient (IQ) match comparison group (n = 17) and a general population comparison group (n = 1155). The DLD, siblings and IQ match groups were assessed on intelligence, language, literacy, social cognition, visual and verbal memory, phonological processing, psychopathology and adult social adaptation. Relative to the comparison groups, the DLD cohort showed a significantly impaired performance on all of the cognitive measures except performance intelligence and visual and verbal memory. Even in their mid thirties, the social adaptation of the DLD cohort continued to be poor compared to the siblings and a general population cohort, particularly in the areas of employment, independent living and relationships. In adult life, three members of the DLD cohort had developed psychoses and one DLD adult had been diagnosed with major depression. No major psychopathology was found in the sibling group. The fourth phase of this study has shown that as adults the DLD cohort continued to have persisting impaired cognitive abilities including language, literacy and specific deficits within phonological processing and social cognition. Furthermore, the DLD cohort experienced significant difficulties in adult social adaptation and are at an increased risk of severe psychiatric disorder. It is proposed that phonological processing and social cognition are two independent causal cognitive deficits in developmental language disorders. The phonological processing deficit causes the persisting language and literacy impairments and the social cognition deficit underpins the social adaptation difficulties which develop later in life. Explanatory theories are put forward to delineate the changing symptomatology within the cognitive, social and psychiatric functioning of developmental language disorders from childhood into adult life.